Strategy for Collaboration in Small Medium Enterprises: A Framework for Strategic Partnership (A Case Study in Jakarta and Bandung Fashion Industry) - Thahira, Asyifa Violanda; Larso, Dwi (Journal of Innovation, Business and Entrepreneurship, 2019)
Abstract. The majority of firms in Indonesia which is categorized as SME are contributing to Indonesia's economic development by creating more job opportunities and thus help the country on tackling down the unemployment rate. Local SMEs nowadays are competing with international SME's, which deluge in Indonesia’s market. This condition forces local SMEs to be able to seek new innovations to strengthen their branding which can be done through collaboration. Performing a collaboration can help SMEs to increase their ability in entering a new market and increasing their business performance, the problem, however, is that SMEs’ obstacle in identifying potential partners and the management process during the collaboration. This research aims to understand the effective and beneficial collaboration to create and inspire the collaboration strategy for fashion SMEs. The primary data gathered is from interviewing the Indonesian fashion small enterprise who accomplished a successful collaboration. The data was analyzed through the transcript and coding method. To obtain the advantages of collaboration, SMEs implemented the strategy compatible with each company’s capability to create an effective work environment and having good relationships among the member of the collaboration. A successful collaboration leverages the company performance in terms of brand awareness and profit of a company.Keywords: Collaboration, Fashion Industry, Small Medium Enterprise, Performance, Collaboration Strategy